2017
DOI: 10.1073/pnas.1621071114
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized practice helps bearded capuchin monkeys learn to extend attention while learning a tradition

Abstract: Culture extends biology in that the setting of development shapes the traditions that individuals learn, and over time, traditions evolve as occasional variations are learned by others. In humans, interactions with others impact the development of cognitive processes, such as sustained attention, that shape how individuals learn as well as what they learn. Thus, learning itself is impacted by culture. Here, we explore how social partners might shape the development of psychological processes impacting learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 63 publications
0
34
0
5
Order By: Relevance
“…Other convergences span different ape genera, such as use of fly swats and leaf napkins by both chimpanzees and orangutans; again, these behaviors are neither species instincts nor individually learned, because they are habitual at some locations but are absent in the same species at other locations. Finally there are convergences between apes and other primates, e.g., the use of stones as hammers to break open hard-cased food by distantly related long-tailed macaques (92) and capuchins (3,93).…”
Section: Does Apementioning
confidence: 99%
See 1 more Smart Citation
“…Other convergences span different ape genera, such as use of fly swats and leaf napkins by both chimpanzees and orangutans; again, these behaviors are neither species instincts nor individually learned, because they are habitual at some locations but are absent in the same species at other locations. Finally there are convergences between apes and other primates, e.g., the use of stones as hammers to break open hard-cased food by distantly related long-tailed macaques (92) and capuchins (3,93).…”
Section: Does Apementioning
confidence: 99%
“…This article focuses on great apes: chimpanzee (Pan troglodytes), gorilla (Gorilla gorilla), and orangutan (Pongo pygmaeus). Other primates are dealt with elsewhere in the issue (3,4). Despite an early report (5), we still know little about cultural phenomena in chimpanzees' rarer sister species, the bonobo (Pan paniscus) so bonobos are omitted here.…”
mentioning
confidence: 99%
“…Hundreds of laboratory experimental studies have demonstrated social learning and transmission in a wide variety of animals. Social learning is now extensively documented in mammals (29), with a particular intensity of research studies in primates (30)(31)(32)(33) and cetaceans (34)(35)(36)(37), in birds (38)(39)(40)(41), in fish (42), and in insects (43,44). The fact that social learning has been shown to play important roles spanning multiple functional contexts (25)(26)(27)(28) suggests that many animals are not simply acquiring one or a few behavioral patterns socially, but rather that social learning is central to their acquisition of adaptive behavior.…”
Section: The Discovery Of Widespread Animal Culturementioning
confidence: 99%
“…As in the capuchin study of Fragaszy et al (32), the psychological and social processes that allow human culture to be so distinctive need to be examined as individuals' life histories unfold, and the affordances of the culture in which they develop are selectively assimilated and further modified. On the one hand, these processes are part of our species' biology, their properties shaped during the millennia of evolutionary time over which our ancestors became increasingly and intensively dependent on cumulative cultural inheritance (54,56,57).…”
Section: Human Culture Is Specialmentioning
confidence: 99%
See 1 more Smart Citation